Pengaruh Edukasi Gizi Seimbang Terhadap Pengetahuan Dan Sikap Anak Di Sekolah Dasar Sejahtera IV Bandar Lampung - Ernawati Siagian; Sherly Manurung (LPPI UMN AL WASHLIYAH, 2024)
Background: Balanced nutrition is one of the things that the government pays special attention to, considering that there are still many school-age children who are considered not to have balanced nutrition, one of the government's efforts to support improving children's balanced nutrition is by providing balanced nutrition education. Objective: This study aims to determine the effect of balanced nutrition on the knowledge and attitudes of children at the Sejahtera IV elementary school in Bandar Lampung. Method: This research is a quantitative experimental study with one pretest and posttest group on 40 elementary school age children in grades 4-6, which was carried out on May 2024 at SD Sejahtrera IV Bandar Lampung. The data obtained using a questionnaire were then processed using SPSS software. and presented in table form which will then be explained further. Results: The results of this study show an increase in knowledge and attitudes after education with a significant influence between balanced nutrition education and knowledge (p-value 0.029, 0.002, 0.000 (<0.05) and there is no significant influence between balanced nutrition education and children's attitudes (p-value 0.134, 0.132, 0.522 (>0.005)). Conclusion: From the results of this research, it was found that balanced nutrition education for children is very important in improving children's knowledge and attitudes. Keywords: Balanced Nutrition Education, Knowledge, Attitude